SIMULATION AND ANALYSIS OF ELECTRIC BUS FOR EXTENSION OF OPERATION RANGE AND DURATION - NUREEN, MUHAMMAD ZIQQRY (Universiti Teknologi PETRONAS, 2017)
Electric ground transportation is starting to have presence in Malaysia. One area is public transit bus, where significant benefits of reduction on dependence on fossil-fuel powered transport can be realized, not to mention major emissions reduction. Possibilities include OEM electric bus or retrofit-converted electric bus where a conventional bus is converted into an electric bus by replacing the conventional combustion engine and transmission with an electric powertrain AND transmission. To extend the range of the electric bus, composite power system is planned which is investigated by simulation using the software ADVISOR, on Matlab-Simulink platform. ADVISOR is a computational program which can be used to simulate an actual vehicle or bus. In this software, the author configures an electric bus simulation model according to the actual physical bus and simulate actual drive cycle according to the real-world bus route. In addition, the author performs simulation runs and analyze the effects of varying control parameters on battery consumption and range. The expected result is by varying control parameters on battery power consumption, the electric bus’s range can be extended so that few more cycles can be obtained with a single charge at the charging station, and the bus can continue to operate without going back to the charging station.